The new experiment WAGASCI for water to hydrocarbon neutrino cross section measurement using the J-PARC beam. Issue 1 (January 2016) - Ovsiannikova, T; Antonova, M; Bronner, C; Blondel, A; Bonnemaison, A; Cornat, R; Cadoux, F; Chikuma, N; Cao, S; Drapier, O; Izmaylov, A; Ichikawa, A K; et al.
Abstract: The T2K (Tokai-to-Kamioka) is a long baseline neutrino experiment designed to study various parameters that rule neutrino oscillations, with an intense beam of muon neutrinos. A near detector complex (ND280) is used to constrain non-oscillated flux and hence to predict the expected number of events in the far detector (Super-Kamiokande). The difference in the target material between the far (water) and near (scintillator, hydrocarbon) detectors leads to the main non-canceling systematic uncertainty for the oscillation analysis. In order to reduce this uncertainty a new water grid and scintillator detector, WAGASCI, has been proposed. The detector will be operated at the J-PARC neutrino beam line with the main physics goal to measure the charged current neutrino cross section ratio between water and hydrocarbon with a few percent accuracy. Further physics program may include high-precision measurements of different charged current neutrino interaction channels. The concept of the new detector will be covered together with the actual construction plan.